2018
DOI: 10.1186/s13104-018-3705-y
|View full text |Cite
|
Sign up to set email alerts
|

Ocular bacterial infections and antibiotic resistance patterns in patients attending Gondar Teaching Hospital, Northwest Ethiopia

Abstract: ObjectivesEmpirical selections of antimicrobial therapy based on clinical observations are common clinical practices in Ethiopia. This study identified common external ocular infections and determined antibiotic susceptibility testing in northwest Ethiopia.ResultsAmong 210 patients studied, conjunctivitis 32.9%(69), blepharitis 26.7%(56), dacryocystitis 14.8%(51), blepharoconjunctivitis 11.9%(25), and trauma 10.0%(21) were the most common external ocular infections. Pathogenic bacteria were isolated among 62.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
6
26
0
Order By: Relevance
“…The presence of external ocular infections were clinically assessed by ophthalmologist with thoroughly examination of all patients using a slit lamp microscope [ 8 ]. Conjunctival and eyelid swabs were collected using sterile cotton swab pre-moistened with sterile physiological saline [ 17 ]. Pus from lacrimal sac was collected using dry sterile cotton swab by applying pressure over the lacrimal sac and allowing the purulent material to reflux through the lacrimal punctum.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of external ocular infections were clinically assessed by ophthalmologist with thoroughly examination of all patients using a slit lamp microscope [ 8 ]. Conjunctival and eyelid swabs were collected using sterile cotton swab pre-moistened with sterile physiological saline [ 17 ]. Pus from lacrimal sac was collected using dry sterile cotton swab by applying pressure over the lacrimal sac and allowing the purulent material to reflux through the lacrimal punctum.…”
Section: Methodsmentioning
confidence: 99%
“…Coagulase-negative Staphylococcus is one of the most commonly isolated bacteria in the ocular infections. 19,20 Belyhun et al 21 reported that this bacterium was isolated in 29% of blepharitis. Teweldemedhin et al 22 described quite similar results in another study.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria, viruses, parasites and fungi are capable of breaching the BRB and infecting retina. This may cause inflammation and ocular infections like conjunctivitis, endophthalmitis, and keratitis which are most commonly caused by bacteria and viruses (Singh et al 2017;Belyhun et al 2018).…”
Section: Sars Cov-2 and The Blood-retinal Barriermentioning
confidence: 99%